Higher Order Propagation Modes Error and Its Compensation - Zaichenko, O. B.; Klyuchnik, I. I.; Martynenko, L. G. (My University, 2012)
The physical and mathematical and metrological model of higher order propagation modes in multiprobe microwave multimeter with three sensors was composed. The higher order propagation modes error estimation, which is proposed, minimizes error by shifting sensors from the middle of the waveguide broad wall to the periphery, without changing the distance between the sensors along the direction of energy propagation through the waveguide.
Keywords: higher order propagation modes; multiprobe microwave multimeter; error